Framework de controle e gerenciamento inteligentes para estações de recarga de veículos elétricos utilizando protocolo OCPP - Martins, Henrique Horquen (2023)
The transport sector has an important role in the development of the economy, the growth of this market, however, has always been side by side with the productive chains of fossil fuels through vehicles with internal combustion engines. However, due to the increase in world awareness about the pollution caused by the consumption of fossil fuels and the drop in the value of batteries, electric vehicles have become an option to be adopted to reduce the emission of these polluting gases. However, in order to electrify the car fleet, it is necessary to develop the basic infrastructure that supplies energy to these vehicles, for this reason, the installation of charging stations is a key point for the adoption of this new technology. This dissertation presents a methodology for intelligent management of electric vehicle chargers using the OCPP 1.6j protocol. The dissertation was developed in two stages, the first stage in a simulated environment, where the services and architecture of the OCPP server were created, in this stage tests and validations of the functionalities that the protocol makes available were also carried out. The second step is related to the integration in real chargers, where the first charger was a single-phase model of slow charging in alternating current. The next integrated chargers were the fast chargers that constitute the first electroway in Rio Grande do Sul that connects the center of the state to the coast. The Framework was developed to support different agents in the system, where each agent can designate limitations on the use and power of the charging stations. The case study showed a good management of the charging stations, in all, the system was implemented in 9 chargers of different models. Operating daily and in real time, the system received essential feedback for the creation of new functionalities that increased user support and control of charging station operators.